Effect of a cervical collar on head and neck acceleration profiles during emergency spinal immobilisation and extrication procedures in elite football (soccer) players: protocol for a randomised, controlled cross-over trial - Callaghan, M. J.; Hughes, T.; Davin, J.; Hayes, R.; Hough, N.; Torpey, D.; Perry, D.; Dawson, S.; Murray, E.; Jones, R. K. (BMJ Open Sport & Exercise Medicine, 2021)
When immobilisation after a cervical spine or head injury is required, the role of the rigid cervical collar is unclear and controversial. There is a need for further studies investigating the use of a rigid cervical collar when head and neck trauma occurs in sport. This study will compare present practice (immobilisation with a cervical collar) to the same procedure without a collar during a simulated spinal immobilisation and extraction scenario from the field of play to the side-line in football (soccer). It will use a prospective cohort within-subjects cross over randomised, controlled trial design. Healthy participants will assume the role of players with a head or neck injury. Clinical practitioners will perform the immobilisation and extrication procedure according to current clinical guidelines. Three dimensional linear and angular acceleration profiles of the head and torso will be measured and the time taken to complete the procedure. The interventions will be a `cervical collar` or `no collar` in random order. Data from the IMUs will be transferred wirelessly to a computer for analysis. Accordingly, within-subject differences between each condition (collar vs no collar) will be assessed with parametric or non-parametric inferential statistics. Statistical significance will be set at p<0.05.